2002
DOI: 10.1186/1471-230x-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Are proton pump inhibitors the first choice for acute treatment of gastric ulcers? A meta analysis of randomized clinical trials

Abstract: BackgroundGastric ulcers are a frequent problem in the United States. Proton pump inhibitors have been shown to increase healing rates and improve clinical symptoms. The objective of this study is to compare gastric ulcer healing rates for patients treated with a proton pump inhibitor (PPI) (omeprazole, rabeprazole, pantoprazole, or lansoprazole), an histamine 2- receptor antagonist (ranitidine) or placebo.MethodsA literature search was conducted to identify randomized, controlled clinical trials that included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…Comment: We recommend PPIs because several metaanalyses demonstrated that the ulcer-healing rate of PPIs was significantly higher than that of H 2 RAs [48][49][50][51]. When PPIs cannot be prescribed due to allergy, for example, H 2 RAs are recommended.…”
Section: Non-eradication Therapymentioning
confidence: 99%
“…Comment: We recommend PPIs because several metaanalyses demonstrated that the ulcer-healing rate of PPIs was significantly higher than that of H 2 RAs [48][49][50][51]. When PPIs cannot be prescribed due to allergy, for example, H 2 RAs are recommended.…”
Section: Non-eradication Therapymentioning
confidence: 99%
“…Optically active sulfoxides, [5][6][7][8][9][10] in general, represent an important class of pharmaceuticals and drug intermediates. [11] They often play an important role as therapeutic agents, such as anti-ulcer (proton pump inhibitors), [12][13][14][15][16] antibacterial, anti-atherosclerotic, [17][18][19] anthelmintic, [20] Adv. Synth …”
Section: Introductionmentioning
confidence: 99%
“…PPIs were also better than ranitidine in healing gastric ulcers-the pooled relative risk (RR) of all PPIs being 1.33 at 4 weeks-as evidenced in a meta-analysis of 16 trials [12]. They were also found to be better in Helicobacter pylori eradication as seen in a meta-analysis of twenty studies in which the eradication rates with PPIs or H 2 RAs plus antibiotics were 74% and 69%, respectively [13].…”
Section: Introductionmentioning
confidence: 91%